2009
DOI: 10.1007/s12239-009-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Design of conformal cooling channels for an automotive part

Abstract: The cooling system plays a crucial role in determining the productivity and quality of an injection molding process. With the current growth of Solid Freeform Fabrication (SFF) techniques, mold designers have been striving for not only improvement in cooling system performance but also for a method to do so automatically. In this paper, a method is proposed for developing a conformal cooling system that facilitates uniform cooling over the entire mold surface with minimum cycle time. Based on the temperature d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 10 publications
0
35
0
1
Order By: Relevance
“…The efficiency of the conventional straight drilled and CCC was compared with results such as warpage and cooling time using Moldflow software. 10,12,36 Blow molding Blow molding is a process to produce hollow-shaped parts. The cooling stage takes up approximately twothirds of the complete blow molding cycle.…”
Section: Injection Moldingmentioning
confidence: 99%
“…The efficiency of the conventional straight drilled and CCC was compared with results such as warpage and cooling time using Moldflow software. 10,12,36 Blow molding Blow molding is a process to produce hollow-shaped parts. The cooling stage takes up approximately twothirds of the complete blow molding cycle.…”
Section: Injection Moldingmentioning
confidence: 99%
“…This technique has some benefits such as being easy to connect to simulation program, to render a view of entire design space as well as computational efficiency (Papalambros, 2002;Park, 2007;Wang & Shan, 2007;. The systematic procedure of metamodel-based optimization technique applied to injection molding is depicted in Fig.…”
Section: Simulation-based Optimization Using Metamodeling Techniquesmentioning
confidence: 99%
“…Solid free-from fabrication (SFF) or rapid prototype (RP) techniques have been applied to build this complex cooling system. It was reported that cooling quality is better than that of conventional cooling channels (Sachs et al, 2000;Xu et al, 2001;Ferreira & Mateus, 2003;Dimla et al, 2005;Au & Yu, 2007;Rännar et al, 2007;Park & Pham, 2009;Safullah et al, 2009). Prototyping technologies with metal powder that can make the mold with conformal cooling channels include selective laser sintering (SLS), 3D printing (3DP), electron beam melting, and laser engineered net shaping.…”
mentioning
confidence: 99%
“…On the contrary, with general analysis it is hard to apply this technique to the simulation of RF. Therefore, in most studies, the computational mesh in general analysis has fine elements over the entire sheet (Park & Pham, 2009). …”
Section: Simulation Of Rf Process By General and Specific Analysismentioning
confidence: 99%